The Influence Of Transformational Leadership Style On Work Engagement Mediated By Motivating Language In Mining Industry - Claudia Kaontole, Nicolen; Tajib, Erny (Green Publisher Indonesia, 2023)
This study aims to determine the influence of transformational leadership style on work engagement mediated by motivating language in mining industry. Mining work is a type of heavy work requiring work engagement from the employee in order to achieve the goals of the company, therefore needed a leader who is able to move or direct the employees to be involved in their work, besides that with the existing of a motivating language, it is hoped that employees will be more involved in their work. This research was conducted on 222 mining company employees working in four regions of Indonesia, results obtained that transformational leadership style has a negative and insignificant influence on work engagement, futhermore transformational leadership style has a positive and significant influence on the three motivating language, namely direction-giving language, empathetic language, and meaning-making language, whereas from the third motivating language only direction-giving language has a significant influence on work engagement. Based on the research, it was found that only direction-giving language was able to mediate transformational leadership style on work engagement, Therefore, in order for employees to be more involved in their work and the goals of the company can be achieved, it is important for the leader to maintain and increase direction-giving language.